Four Novel d10 Metal-Organic Frameworks Incorporating Amino-Functionalized Carboxylate Ligands: Synthesis, Structures, and Fluorescence Properties - Xie, Wang; Wu, Jie; Hang, Xiaochun; Zhang, Honghai; shen, Kang; Wang, Zhoulu (Frontiers in Chemistry, 2021)
By employment of amino-functionalized dicarboxylate ligands to react with d10 metal ions, four novel metal-organic frameworks (MOFs) were obtained with the formula of {[Cd(BCPAB)(μ2-H2O)]}n (1), {[Cd(BDAB)]∙2H2O∙DMF}n (2), {[Zn(BDAB)(BPD)0.5(H2O)]∙2H2O}n (3) and {[Zn(BDAB)(DBPB)0.5(H2O)]∙2H2O}n (4) (H2BCPAB = 2,5-bis(p-carbonylphenyl)-1-aminobenzene; H2BDAB = 1,2-diamino-3,6-bis(4-carboxyphenyl)benzene); BPD = (4,4′-bipyridine); DBPB = (E,E-2,5-dimethoxy-1,4-bis-[2-pyridin-vinyl]-benzene; DMF = N,N-dimethylformamide). Complex 1 is a three-dimensional (3D) framework bearing seh-3,5-Pbca nets with point symbol of {4.62}{4.67.82}. Complex 2 exhibits a 4,4-connected new topology that has never been reported before with point symbol of {42.84}. Complex 3 and 4 are quite similar in structure and both have 3D supramolecular frameworks formed by 6-fold and 8-fold interpenetrated 2D coordination layers. The structures of these complexes were characterized by single crystal X-ray diffraction (SC-XRD), thermal gravimetric analysis (TGA) and powder X-ray diffraction (PXRD) measurements. In addition, the fluorescence properties and the sensing capability of 2–4 were investigated as well and the results indicated that complex 2 could function as sensor for Cu2+ and complex 3 could detect Cu2+ and Ag+via quenching effect.